THE INFLUENCE OF LEADERSHIP STYLE, COMPETENCE AND ORGANIZATIONAL CULTURE ON CIVIL SERVENT PERFORMANCE THROUGH WORK MOTIVATION AND JOB SATISFACTION AT REGIONAL IV OFFICE BKN MAKASSAR - Mahmud, Misra; Sapiri, Muhtar; Zaidin, Arifin (Dinasti Publisher, 2021)
This study aimed to analyze the direct impact of leadership style, competence, organizational culture on the employee performance of the Regional IV Office of BKN Makassar and the indirect effect through work motivation and job satisfaction. Using the slovin formula, the number of samples obtained was 90 people. To facilitate the research, observations, questionnaires and documentation were carried out. The data analysis technique used PLS analysis through the outer model, inner model, goodness of fit evaluation, hypothesis testing, and Sobel test. The study results obtained empirical findings that leadership style, competence can significantly affect the improvement of employee performance. Meanwhile, organizational culture had no noticeable impact. The mediation test results showed that the effects of leadership style and competency on employee performance through work motivation was considerable, whereas organizational culture through motivation was not. Leadership style, competence, and organizational culture through job satisfaction all have a significant impact.